'(Simply) the best', or remembering when tina turner met the winfield cup: Nostalgia and the construction of authenticity in rugby league online spaces. Issue 1 (12th July 2020) - Spracklen, Karl; Spracklen, Lee
Abstract: This is an online content analysis using Discourse Tracing to make sense of how rugby league fans talk about changes in the game since the 1980s. Specifically, we are interested in how fans discuss Tina Turner singing '(Simply) the Best' and another song in a famous marketing campaign for Australian rugby league's professional Winfield Cup. We will use comments below the line on YouTube and in two public fan chat-rooms to explore how the remembering the video constructs a shared myth of Australian and British white working-class masculinity. We argue that while alternative constructions of Australian and British masculinity and national identity are present in this nostalgia, there is also a yearning for a time when hegemonic masculinity intersected with white, working-class nationalist identities and which was reflected in the imagery in the promotional videos.